Storage of carbon in natural grasses high andean - Yaranga Cano, Raúl Marino (2013)
The aim of the study was to determine the capacity of storage of carbon in species of grasses natural of high andean, between January of 2012 and March of 2013. They were defined two sampling areas in the districts of Huasicancha and Chicche of the county of Huancayo, Junín. The first of the areas was located in the place Pumahuasi (18L 466456E 8628580N) and the second in Vista Alegre (18L 464886E 8642964N), between 3 845 and 3 870 meters of altitude. 10 plants per species were collected at random, between April and May, considering the moment of maximum growth of the plants. The samples were washed and dried off to the atmosphere during 15 days, being completed the drying in a stove to 60 °C, during 48 hours. The determination of the percentage of dry matter of the samples was carried out by the difference between the initial and final weights. While that the determination of the percentage of carbon was carried out through the method of Walkley-Black. The results of the correlation of weight between air biomass and biomass radicular were highly significant r = 0.9856 ** and b = 3.4507. The percentage of the weight of the root regarding that of the air biomass oscillated between 27.93% and 30.20%, respectively. The content of carbon expressed as percentage varied according to the part of the plant and the origin place.